Experiences of Black International Graduate Students: Encounters of Racial Disparities amidst EDI Rhetoric at a Canadian University - Ellis Colley, Vanessa; Nelson, Tenneisha; Palmer-Clarke, Yolanda; Blair, Kenisha (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2025)
International students are integral to Canadian higher education institutions and Canada’s economic gain, contributing $37.3 billion to the economy in 2022, up from $21.6 billion in 2018 (Statistics Canada, 2024). They also add to the cultural enrichment and diversity of institutions and are a major source of bridging the gap in Canada’s labour shortage. This research explored the experiences of Black graduate international students. Grounded in Vygotsky’s sociocultural theory, the researchers centred the voices and perceptions of 12 Black international graduate (BIG) students as they shared their university experiences in a foreign land, rife with unfamiliarity/anomalies. Data were gathered using focus groups and semi-structured interviews to address the question, “What are the experiences of BIG students in the contexts of race, equity, and student support?” Participants candidly shared their university experiences. Interpretive phenomenological analysis (IPA) was used to understand how their lived experiences influenced/impacted their transition and academic milieu. The findings highlighted the emotional effects on participants as they navigate the nuances of international education and suggest the need for increased dynamic student support. Recommendations were made that would contribute to knowledge sharing and empowering universities, particularly student services units, to better understand and better respond to the needs of BIG students.